THE IMPACT OF COMPETENCY, ORGANIZATIONAL CAREER MANAGEMENT AND PERFORMANCE APPRAISAL TOWARDS CAREER PATH ADVANCEMENT ON MILLENNIAL HR PROFESSION WITH ASSIST FROM ORGANIZATIONAL COMMITMENT AS INTERVENING VARIABLE - Jejen Zainal Mutaqin; Chaerudin Chaerudin (Dinasti Publisher, 2020)
These research aims to disclosed and analyzed those influence from competency, Organizational career management and Performance appraisal towards Career path Advancement on millennial HR profession with assist of organizational commitment as intervening variable. These research population were workers / HR profession with category of millennial ages in companies around Jabodetabek with research sample was taken by random sampling as many as 218 people. Data obtained from distributed questionnaires result with analysis methods by SEM using the SmartPLS version 3.2.8 program and The results showed that those variables of competency, organizational career management, and performance appraisal had positive and significant influence against Career path advancement. Alongside with Organizational commitment variable were also positively and significant mediated of those variables towards Career path advancement.